Korelasi Self-efficacy dengan Prokrastinasi Akademik Mahasiswa Sosiologi - Fadli Padila Putra; Eva Latipah; Yayan Suryana (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2023)
The purpose of this study was to determine the correlation between self-efficacy and academic procrastination in college students. The hypothesis put forward is that there is a negative correlation between self-efficacy and student academic procrastination, with the assumption that the stronger the self-efficacy, the smaller the student's academic procrastination. Conversely, the lower the student's self-efficacy, the greater the student's academic procrastination. This research is a correlational study with a sample of 31 people. Purposive sampling is used in the sampling technique. Questionnaires were used to collect data, data processing using the SPSS 21 application was carried out to find the correlation of the two variables. This study obtained Sig. (2-tailed) with a value of 0.000 <0.05 between self-efficacy and academic procrastination, which indicates that there is a significant relationship between self-efficacy and academic procrastination. The Pearson Correlation value between self-efficacy and academic procrastination is -0.611, indicating that there is a strong relationship between self-efficacy and academic procrastination and has a negative sign, which means that the higher the self-efficacy score, the lower the academic procrastination score, or conversely, the lower the self-score efficacy, the higher the value of academic procrastination. ____________________________________________________________ Tujuan dari penelitian ini adalah untuk mengetahui korelasi antara self-efficacy dan prokrastinasi akademik pada mahasiswa. Hipotesis yang diajukan adalah adanya korelasi negatif antara self-efficacy dengan prokrastinasi akademik mahasiswa, dengan asumsi semakin kuat self-efficacy maka semakin kecil prokrastinasi akademik mahasiswa. Sebaliknya, semakin rendah self-efficacy mahasiswa, maka semakin besar prokrastinasi akademik mahasiswa tersebut. Penelitian ini merupakan penelitian korelasional dengan jumlah sampel 31 orang. Purposive sampling digunakan dalam teknik pengambilan sampel. Kuesioner digunakan untuk mengumpulkan data, pengolahan data dengan menggunakan aplikasi SPSS 21 dilakukan untuk mencari korelasi kedua variabel. Studi ini memperoleh Sig. (2-tailed) dengan nilai 0,000 < 0,05 antara self-efficacy dengan prokrastinasi akademik, yang menunjukkan bahwa ada hubungan yang signifikan antara variabel self-efficacy dengan prokrastinasi akademik. Nilai Pearson Correlation antara self-efficacy dengan prokrastinasi akademik adalah -0,611, menunjukkan bahwa terdapat hubungan yang kuat antara self-efficacy dengan prokrastinasi akademik dan bertanda negatif, yang mengandung makna semakin tinggi skor self-efficacy maka semakin rendah skor prokrastinasi akademik, atau sebaliknya semakin rendah skor self-efficacy maka semakin tinggi nilai prokrastinasi akademik.